Determining the diagnostic accuracy of tuning fork weber test and audiometric weber test in conductive hearing loss individuals - Abdullah, Siti Nazira (2020)
Objectives: Weber test is typically conducted using a tuning fork but an audiometer can also be used for a similar purpose. Compared to the tuning fork (TF) test, performing Audiometric Weber (AW) test offers several flexibilities as multiple frequencies can be tested and the sound presentation can be fixed at one intensity level without decay issue. Nevertheless, the performance of TF and AW tests in comparison to pure tone audiometry (PTA) has not been systematically studied. Therefore, the objectives of this study were to determine the accuracy and agreement of TF test in comparison to PTA and to determine the accuracy and agreement of AW test in comparison to PTA. Methods: TFW test was performed according to the established protocol at 256 Hz and 512 Hz. For AW test, a B-71 bone vibrator was placed in the midline of forehead, and 250 Hz and 500 Hz frequencies were tested. The results of TFW and AW tests were then compared with the expected lateralization results. Results: At 256 Hz (or 250 Hz), the overall accuracy values of TFW and AW tests were 81.1% and 86.5%, respectively. At 512 Hz (or 500 Hz), the overall accuracy results of TFW and AW tests were 85.1% and 82.4%, respectively. The kappa statistics revealed substantial agreements between the two tests and PTA (k = 0.63-0.72). Relatively better accuracy results were noted when testing participants with larger air-bone gaps (81.5%-89.1%) compared to those with smaller air-bone gaps (77.7%-88.5%). Conclusion: Both AW and TFW tests are reasonably accurate in assessing patients with CHL. It is recommended for audiologists to perform the simple AW test to verify incomplete or questionable audiograms that are commonly encountered in clinical practice.